Study of Multi-source Fusion B2C Business Process Reengineering of the Petri net Model - Feng Tian (Institute of Advanced Engineering and Science, 2013)
In order to fuse a multi-source B2C E-commerce system, this paper implements a new multi-source fusion B2C mode business system application development, which can provide customers with efficient and reliable comparison and cross-platform business system of choose and buy goods. By analyzing the Multi-source fusion B2C E-commerce system demand of business process reengineering and Petri net theory, the B2C electronic commerce system of multi-source fusion structure is proposed, graphical workflow modeling methods is adopted, the multi-source fusion of B2C business process reengineering Petri model is established, with the help of CPNtool simulation system and the establishment of correlation matrix analysis of the model. The experimental simulation analysis and output of experimental reports indicate that the business processes are properly designed, no deadlocks node exist at runtime, accessibility meets which provides the reference model for the development of multi-source fusion of B2C electronic commerce system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3526